A tree peony RING-H2 finger protein, PsATL33, plays an essential role in cold-induced bud dormancy release by regulating gibberellin content - Mao, Yanxiang; Yuan, Yanping; Gao, Yeshen; Zeng, Lingling; Fan, Siyu; Luo, Jianrang; Sun, Daoyang (Frontiers in Plant Science, 2024)
Bud dormancy is crucial for woody perennial plants to resist low temperature stress in winters. However, the molecular regulatory mechanisms underlying bud dormancy release are largely unclear. Here, a tree peony (Paeonia suffruticosa) transcript ARABIDOPSIS TOXICOS EN LEVADURA 33 (PsATL33), encoding a RING-H2 finger protein, was selected from previously generated RNA sequencing data of chilling-treated buds. The objective of this study is to investigate the role of PsATL33 in the regulation of cold-induced bud dormancy release. Subcellular localization assay revealed that PsATL33 was localized into the nucleus and plasma membrane. Reverse transcription-quantitative PCR analysis showed that PsATL33 was dramatically up-regulated during cold-triggered bud dormancy release. Exogenous treatments with gibberellin (GA3) increased but abscisic acid (ABA) inhibited the transcription of PsATL33. Ectopic transformation assay indicated that overexpression of PsATL33 in petunia promoted seed germination, plant growth, and axillary bud break. Silencing of PsATL33 in tree peony through virus-induced gene silencing assay delayed bud dormancy release. TRV-PsATL33-infected buds exhibited reduced expression levels of dormancy break-related genes EARLY BUD-BREAK 1 (PsEBB1) and CARBOXYLESTERASE 15 (PsCXE15). Silencing of PsATL33 decreased the accumulation of bioactive GAs, GA1 and GA3, rather than ABA. Transcript levels of a couple of genes involved in GA biosynthesis and signaling, including GA20-OXIDASE 1 (PsGA20ox1), GA3-OXIDASE 1 (PsGA3ox1), PsGA3ox3, GA2-OXIDASE 1 (PsGA2ox1), and GA-INSENSITIVE 1A (PsGAI1A), were changed by PsATL33 silencing. Taken together, our data suggest that PsATL33 functions as a positive regulator of cold-induced bud dormancy release by modulating GA production.